Transporter and metabolizer gene polymorphisms affect fluoroquinolone pharmacokinetic parameters - Annisa, Nurul; Barliana, Melisa I.; Santoso, Prayudi; Ruslami, Rovina (Frontiers in Pharmacology, 2022)
Tuberculosis (TB) is an infectious disease that occurs globally. Treatment of TB has been hindered by problems with multidrug-resistant strains (MDR-TB). Fluoroquinolones are one of the main drugs used for the treatment of MDR-TB. The success of therapy can be influenced by genetic factors and their impact on pharmacokinetic parameters. This review was conducted by searching the PubMed database with keywords polymorphism and fluoroquinolones. The presence of gene polymorphisms, including UGT1A1, UGT1A9, SLCO1B1, and ABCB1, can affect fluoroquinolones pharmacokinetic parameters such as area under the curve (AUC), creatinine clearance (CCr), maximum plasma concentration (Cmax), half-life (t1/2) and peak time (tmax) of fluoroquinolones.